Alternativas y dificultades de lactancia materna en Ecuador - Freire Paredes, Jazmín Elizabeth (2017)
Breastfeeding in Ecuador has become a fundamental process, thus breasmilk is the apropriate nutritional complement for the first six monts of a newborn, it has all the proteins and minerals the baby needs for a healthy life. This research proposes to analize and to learn all the characteristics, options and problematics of breastfeeding, besides all the speeches and the debates that exist about this topic in Ecuador, and especifically in the city of Quito. The research suggests to inquire base concepts such as, that in the first six months of life of a newborn breastmilk should be his only nourishment and this period could extend until the baby is two years old, according to the World Health Organization (WHO). The present work shows likewise a qualitative comparison between breastmilk and formula and observes the consequenses babies have being fed with each one of them: two cases will be presented with the testimony of mothers.